(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This research aims to provide a detailed analysis of the anatomical pathways of the lower thyroid artery and the lower sciatic nerve. Understanding the precise courses of these vital structures is crucial for surgical procedures, nerve blocks, and overall medical knowledge. Employing a combination of cadaveric dissections, imaging techniques, and literature review, this study aims to contribute valuable insights into the anatomical variations and clinical implications associated with these structures.